Measuring the Success of PeduliLindungi Application Use for Supporting COVID-19 Prevention: A Case Study among College Students in Jakarta, Indonesia - Nurmansyah, Mochamad Iqbal; Rosidati, Catur; Yustiani, Yustiani; Nasir, Narila Mutia (Kesmas, 2022)
The Indonesian Government has launched PeduliLindungi (PL) mobile apps as a COVID-19 preventive tool. This study aimed to describe the PL utilization and determine the factors influencing its successful use among college students. This study used a cross-sectional design and a total population sampling at a university in the Special Capital Region of Jakarta, Indonesia. The Delone and Mclean Information System Success Model was adopted to measure the use of the apps. The Spearman’s rank correlation test was performed to determine the relationship between two variables. Furthermore, 354 respondents participated in this study. The respondents used the apps mostly to display the vaccination certificate and check in/out from public facilities. The overall user satisfaction value towards the application was 3.83+0.76. The system quality (r = 0.621, p-value<0.001) and information quality (r = 0.626, p-value<0.001) were associated with the user satisfaction while the user satisfaction (r = 0.471, p-value<0.001), was correlated to the perceived benefit. In brief, perceived benefit was positively correlated with the user’s satisfaction, whereas user satisfaction was positively correlated with self-efficacy, system quality, and information quality.